2009
DOI: 10.1002/erv.975
|View full text |Cite
|
Sign up to set email alerts
|

Exploring quality of life in the eating disorders

Abstract: Severity of the eating disorder and BMI were predictors of low quality of life. Duration of illness, contrary to clinical expectations was not a significant predictor of poor quality of life. In terms of differences across diagnostic groups, individuals with a diagnosis of anorexia nervosa in this sample were found to have lower psychological and physical/cognitive quality of life than those with an EDNOS or BN diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 30 publications
2
41
2
9
Order By: Relevance
“…An irrational overvaluation of the importance of controlling food, weight, and body shape represent the specific clinical features [1]. Severe EDs impair quality of life and interpersonal relations [2], and increase the number of productive years lost to disability [3].The standardized mortality rate is about five times higher than in the general population [4,5], and it takes six to nine years before 70% of the patients no longer meet the diagnostic criteria for an ED [6,7].Comorbid personality disorders (PDs) are frequently encountered in the treatment of EDs, and may become as protracted and impairing as the EDs. Previous studies [8][9][10] show that a comorbid borderline, avoidant, or obsessive-compulsive PD may worsen the long-term treatment-outcome of EDs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An irrational overvaluation of the importance of controlling food, weight, and body shape represent the specific clinical features [1]. Severe EDs impair quality of life and interpersonal relations [2], and increase the number of productive years lost to disability [3].The standardized mortality rate is about five times higher than in the general population [4,5], and it takes six to nine years before 70% of the patients no longer meet the diagnostic criteria for an ED [6,7].Comorbid personality disorders (PDs) are frequently encountered in the treatment of EDs, and may become as protracted and impairing as the EDs. Previous studies [8][9][10] show that a comorbid borderline, avoidant, or obsessive-compulsive PD may worsen the long-term treatment-outcome of EDs.…”
mentioning
confidence: 99%
“…An irrational overvaluation of the importance of controlling food, weight, and body shape represent the specific clinical features [1]. Severe EDs impair quality of life and interpersonal relations [2], and increase the number of productive years lost to disability [3].…”
mentioning
confidence: 99%
“…In the study by Bamford et al, predictors of low quality of life in the study group of women were found to be severity of the eating disorders and the BMI, whereas -contrary to clinical expectations -the duration of the disease did not reveal itself as a major predictive factor in this respect [18].…”
Section: Anorexia and Bulimiamentioning
confidence: 66%
“…Severity of ED symptomatology, especially low body mass index (BMI), but not duration of illness has been found to be predictive of low QoL [24]. Moreover, in terms of differences across diagnostic groups, individuals with a diagnosis of AN were found to have lower psychological and physical/ cognitive QoL than those with an OSFED or BN diagnosis [24]. Even after long-term treatment or recovery from EDs, the expatients reported only a slight improvement in their QoL [18].…”
Section: Quality Of Lifementioning
confidence: 99%